The Impact of the Corona Virus Disease 2019 Pandemic on Chinese Middle School Students’ Self-Perceived Emotional States: A Wuhan Perspective - Huang, Yan; Huang, Jinyan; Wang, Tingting; Xu, Siying; Li, Jialing (Frontiers in Psychology, 2021)
This mixed-methods study examined the impact of the COVID-19 pandemic on 1493 Grades 7, 8, and 9 students’ self-perceived emotional states in Wuhan, China when it was locked down for the pandemic on January 23, 2020 and when the lockdown was lifted on April 8, 2020, as well as the changes of their emotional states over the one-year period after the lockdown was lifted. A five-point Likert scale survey was administered to the participants between March 1 and April 1, 2020 when Wuhan was blocked down; and three focus group interviews were conducted between May 1 and May 31, 2021, one year after the lockdown was lifted. The results showed that these students in Wuhan experienced feelings of loss of control and negative emotions when the city was locked down and they were home quarantined; furthermore, there were significant differences for their self-perceived feelings of loss of control and negative emotions across demographic variables of gender, grade level, physical activity, social economic status, and family cohesion; finally, their emotional states changed substantially at different time nodes during this pandemic. Implications for students, parents, and schools are discussed.